2019
DOI: 10.3390/molecules24142545
|View full text |Cite
|
Sign up to set email alerts
|

PPARs as Nuclear Receptors for Nutrient and Energy Metabolism

Abstract: It has been more than 36 years since peroxisome proliferator-activated receptors (PPARs) were first recognized as enhancers of peroxisome proliferation. Consequently, many studies in different fields have illustrated that PPARs are nuclear receptors that participate in nutrient and energy metabolism and regulate cellular and whole-body energy homeostasis during lipid and carbohydrate metabolism, cell growth, cancer development, and so on. With increasing challenges to human health, PPARs have attracted much at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 166 publications
(200 reference statements)
0
115
0
2
Order By: Relevance
“…Since their identification as receptors responsible for peroxisome proliferation in 1990, research on peroxisome proliferator‐activated receptors (PPARs) has increased dramatically, revealing more and more fascinating functions in human biology. This research also has revealed that dysregulation of PPARs is connected to the development of a wide range of human diseases, including atherosclerosis, obesity, type 2 diabetes and many others …”
Section: Ppars In Human Biology and Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Since their identification as receptors responsible for peroxisome proliferation in 1990, research on peroxisome proliferator‐activated receptors (PPARs) has increased dramatically, revealing more and more fascinating functions in human biology. This research also has revealed that dysregulation of PPARs is connected to the development of a wide range of human diseases, including atherosclerosis, obesity, type 2 diabetes and many others …”
Section: Ppars In Human Biology and Skinmentioning
confidence: 99%
“…PPARs are nuclear hormone receptors abundantly expressed in tissues that display high fatty acid metabolism, including human skin and its appendages . Three different isoforms of PPARs exist—PPAR‐α, PPAR‐β/δ and PPAR‐γ, which demonstrate diverse functional capabilities, including—to name but a few examples—the control of lipogenesis, cell cycle and inflammatory gene expression (Figure ) …”
Section: Ppars In Human Biology and Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, compounds 1 and 2 were evaluated for agonist activity to peroxisome proliferator-activated receptors (PPARs) because similar oxo fatty acids are known to act as PPAR agonists [42]. PPARs are ligand-activated transcription factors playing key roles in lipid and carbohydrate metabolism [43,44]. PPARα upregulates lipid uptake and β-oxidation of fatty acids, whereas PPARγ promotes adipocyte differentiation and adipokine production in adipose tissues to improve insulin sensitivity in diabetic patients [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…The peroxisome proliferator‐activated receptor δ (PPARδ) is a nuclear receptor and belongs to the PPAR family, which includes PPARα, PPARγ and PPARδ. [ 13–15 ] The agonist of PPARα (fenofibrate) or PPARγ (rosiglitazone) has been widely used to the treatment of dyslipidemia and T2DM, but the adverse effects limited its application. [ 16–18 ] PPARδ, another member of the PPAR family, exhibits high expression levels not only in liver but also in skeletal muscle and macrophages, and its activation ameliorates anti‐inflammation, insulin sensitization and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%